Leader Member Exchange dan Work Engagement sebagai Kunci Job Crafting: Studi pada Karyawan di Indonesia - Khairina Widya Primandari Haryono; Lupi Yudhaningrum; Nazir Ultama Anugrah; Irma Rosalinda Lubis; Muhammad Irfan Pratama Fasa (Universitas Mercu Buana, 2025)
This study examined the role of Leader–Member Exchange (LMX) and work engagement as predictors of job crafting among employees in Indonesia. Grounded in the Job Demands–Resources model, the research was conducted to address the limited empirical evidence on the simultaneous contribution of interpersonal (LMX) and intrapersonal (work engagement) resources to proactive work behaviour in a collectivistic, hierarchical work culture. It was hypothesised that LMX and work engagement would each, and jointly, have a positive effect on job crafting. The study employed a quantitative correlational design using an online survey of 280 employees who met predetermined work-tenure criteria. LMX, work engagement, and job crafting were measured with validated Likert-type scales and analysed using multiple linear regression. The findings showed that both LMX and work engagement significantly predicted job crafting, with work engagement emerging as the stronger predictor; together, both variables explained 52.3% of the variance in job crafting. These results highlight the importance of strengthening employees’ psychological engagement alongside high-quality leader–member relationships to foster adaptive, self-initiated changes in work roles within Indonesian organisations.